Towards an Aggregate Conceptual Model of Silence at Workplace: Multi-Level Phenomenon - Haseeb, Muhammad Abdul; Jamal, Waseef (International Journal of Psychosocial Rehabilitation, 2020)
The prevalence of silence at the workplace is a common phenomenon and affects not only organizational outcomes but individual job outcomes and attitudes. Which shows its multiple levels affect. Additionally, the antecedents of such situations are embedded in both individuals and organizations too. To date, a greater number of studies have focused on the pragmatic nature of silence, developing models only for this very form of silence. While "Nonpragmatic silence” remains unattended. Consequently, this paper applies ABC model and Multiple level analysis to get a better understanding of silence at the workplace and develop a conceptual framework for the same, which includes both Pragmatic Silence(PS) and Non-pragmatic silence(NPS). Moreover, antecedents and consequences have been bifurcated.